Assessment Accommodations for Foreign Pupils in the Light of Educational Justice: Empirical Research among Slovenian Primary School Teachers - Mojca Žveglič Mihelič (Center for Educational Policy Studies Journal)
The starting points of primary school pupils in a foreign country differ significantly from those of native pupils. In Slovenia, the knowledge of pupils who are foreign citizens (foreign pupils) may be assessed with different accommodations for no more than two years. The presented research conducted on a representative sample of 697 Slovenian primary school teachers addresses their perspectives, using a questionnaire, on assessment accommodations for foreign pupils. The following research questions are answered: 1) What are teachers’ perceptions of assessment accommodations for foreign pupils; are there differences between teachers who had recently taught foreign pupils and those who had not? 2) Do generalist teachers have different perceptions than subject teachers do? 3) What kind of assessment accommodations do teachers practice for these pupils after the expiration of the two-year period; do generalist and subject teachers act differently? 4) Do teachers perceive assessment accommodations as being just? We demonstrate that teachers who have recent experience of teaching foreign pupils are more aware of the need for assessment accommodations than those who do not. The majority of the  teachers accommodate assessment and grading even after the two-year period, especially generalist teachers. Additionally, some of them have lower expectations with regard to achieving knowledge standards for these pupils. While the majority of the teachers perceive accommodated assessment as being just, they are unsure of whether the period of allowed adjustments should be longer. This raises the questions about teachers’ understanding of educational justice and the application of the principle of justice in practice.